Effect of Pre- and In-Hospital Delay on Reperfusion in Acute Ischemic Stroke Mechanical Thrombectomy. Issue 10 (October 2020) - Kaesmacher, Johannes; Maamari, Basel; Meinel, Thomas R.; Piechowiak, Eike I.; Mosimann, Pascal J.; Mordasini, Pasquale; Goeldlin, Martina; Arnold, Marcel; Dobrocky, Tomas; Boeckh-Behrens, Tobias; Berndt, Maria; Michel, Patrik; et al.
Abstract : Background and Purpose: Post hoc analyses of randomized controlled clinical trials evaluating mechanical thrombectomy have suggested that admission-to-groin-puncture (ATG) delays are associated with reduced reperfusion rates. Purpose of this analysis was to validate this association in a real-world cohort and to find associated factors and confounders for prolonged ATG intervals. Methods: Patients included into the BEYOND-SWIFT cohort (Bernese-European Registry for Ischemic Stroke Patients Treated Outside Current Guidelines With Neurothrombectomy Devices Using the Solitaire FR With the Intention for Thrombectomy; https://www.clinicaltrials.gov ; Unique identifier: NCT03496064) were analyzed (n=2386). Association between baseline characteristics and ATG was evaluated using mixed linear regression analysis. The effect of increasing symptom-onset-to-admission and ATG intervals on successful reperfusion (defined as Thrombolysis in Cerebral Infarction [TICI] 2b-3) was evaluated using logistic regression analysis adjusting for potential confounders. Results: Median ATG was 73 minutes. Prolonged ATG intervals were associated with the use of magnetic resonance imaging (+19.1 [95% CI, +9.1 to +29.1] minutes), general anesthesia (+12.1 [95% CI, +3.7 to +20.4] minutes), and borderline indication criteria, such as lower National Institutes of Health Stroke Scale, late presentations, or not meeting top-tier early time window eligibility criteria (+13.8 [95% CI, +6.1 to +21.6] minutes). There was a 13% relative odds reduction for TICI 2b-3 (adjusted odds ratio [aOR], 0.87 [95% CI, 0.79–0.96]) and TICI 2c/3 (aOR, 0.87 [95% CI, 0.79–0.95]) per hour ATG delay, while the reduction of TICI 2b-3 per hour increase symptom-onset-to-admission was minor (aOR, 0.97 [95% CI, 0.94–0.99]) and inconsistent regarding TICI 2c/3 (aOR, 0.99 [95% CI, 0.97–1.02]). After adjusting for identified factors associated with prolonged ATG intervals, the association of ATG delay and lower rates of TICI 2b-3 remained tangible (aOR, 0.87 [95% CI, 0.76–0.99]). Conclusions: There is a great potential to reduce ATG, and potential targets for improvement can be deduced from observational data. The association between in-hospital delay and reduced reperfusion rates is evident in real-world clinical data, underscoring the need to optimize in-hospital workflows. Given the only minor association between symptom-onset-to-admission intervals and reperfusion rates, the causal relationship of this association warrants further research. Registration: URL: https://www.clinicaltrials.gov . Unique identifier: NCT03496064. Abstract : Supplemental Digital Content is available in the text.